School Cafeteria: Time and Educational Space - González-Garzón, Mª Leonor; Laorden Gutiérrez, Cristina; Pérez-López, Concepción; Pérez López, Montserrat (Pulso. Revista de educación, 2003)
The school canteen in early childhood and primary education institutions is a complementary service that has a significant social component, serving as a support system that enhances the overall quality of these establishments. This article examines the current state of this service, its legal framework, the gathering of various ideas and experiences from different schools, and a proposed strategy for optimising this educational space and time. It is our belief that school canteens should not be viewed in isolation from management teams, teaching staff, families, or industry stakeholders... rather, they should be regarded as a globalising resource and element for providing high-quality education.